The Medical Library Association Guide to Finding Out About Complementary and Alternative Medicine - Melissa L. Gold (Issues in Science and Technology Librarianship, 2010)
The article reviews the book "The Medical Library Association Guide to Finding Out About Complementary and Alternative Medicine: The Best Print and Electronic Resources," by Gregory A. Crawford.